2014
DOI: 10.1021/ic501408r
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Computational and Experimental Protocol for Understanding Rh(III) Speciation in Hydrochloric and Nitric Acid Solutions

Abstract: Platinum group metals (PGMs), including rhodium, generated by the fission of (235)U are present in significant quantities within spent nuclear fuel located on power generation sites in the United States, the amount of which is expected to exceed natural reserves by 2030. Yet, spent fuel raffinates are highly acidic media that may result in complex speciation of the PGM. This work provides an understanding of Rh(III) speciation up to 9 M HCl and HNO3, and utilizes a combination of ultraviolet-visible (UV-vis) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…This is indicative of inner-sphere binding in the [RhCl3(L4)] complex and in the [RhCl3(L2)] complex formed over a long time period, which is in accordance with the FT-IR measurements. [25][26] but is contrary to studies using UV/Vis spectroscopy and DFT calculations [6][7] Some of these disparities may have resulted from different Rh sources (RhCl3 versus Na3RhCl6), or differences in concentration and sample preparation. Thus, whilst these results find agreement with the earlier studies that Rh(III) speciation in HCl media is complex, under the extraction operating conditions for L2 explored in this paper it is likely that 50% of the Rh(III) present will be in the form of the dianion, and thus be extracted in a 1:2 ratio with L2, in agreement with the slope analysis presented in Figure 2.…”
Section: Esi-mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This is indicative of inner-sphere binding in the [RhCl3(L4)] complex and in the [RhCl3(L2)] complex formed over a long time period, which is in accordance with the FT-IR measurements. [25][26] but is contrary to studies using UV/Vis spectroscopy and DFT calculations [6][7] Some of these disparities may have resulted from different Rh sources (RhCl3 versus Na3RhCl6), or differences in concentration and sample preparation. Thus, whilst these results find agreement with the earlier studies that Rh(III) speciation in HCl media is complex, under the extraction operating conditions for L2 explored in this paper it is likely that 50% of the Rh(III) present will be in the form of the dianion, and thus be extracted in a 1:2 ratio with L2, in agreement with the slope analysis presented in Figure 2.…”
Section: Esi-mass Spectrometrymentioning
confidence: 99%
“…[RhCln(H2O)6-n] 3-n , can form. 6,7,8 This variety of species makes Rh separation using solvent extraction difficult as the tailoring of the organic-phase extractant becomes impractical. The chloridometalates are kinetically inert, so in order to gain separation extractants are designed to target the outer coordination sphere; the presence of multiple aquated chloridometalate species is therefore a significant complicating factor in extractant design.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11] Crucial for establishing the mechanism of action of platinum complexes is their speciation in water solution, which has been studied in detail by several techniques. [12][13][14][15][16] Nuclear Magnetic Resonance (NMR) spectroscopy, in particular the multinuclear variants, is an useful tool for understanding the aquation of complexes under physiological conditions, [17][18] and very convenient to connect theory and experiment. 19 For platinum complexes containing aliphatic amines in a trans configuration, NMR studies demonstrated a direct relationship between the aquation process, the complexes' structure and their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies can supplement experimental work in this area and can help to create a holistic understanding of the PGM solution chemistry. Recently, Samuels et al provided an understanding of Rh III speciation up to 9 m HCl and HNO 3 using a combination of ultraviolet‐visible spectroscopy and capillary zone electrophoresis data, along with computationally predicted thermochemistry to approximate the relative concentrations of potential species in solution as a function of acid concentration.…”
Section: Introductionmentioning
confidence: 99%